Extracranial abscopal effect induced by combining immunotherapy with brain radiotherapy in a patient with lung adenocarcinoma: A case report and literature review - Lin, Xinqing (Thorac Cancer, 2019)
An extracranial abscopal effect induced by brain radiotherapy is particularly unusual because of the brain's distinctive immune microenvironment. We report a case of an extracranial abscopal effect in a 71‐year‐old male patient with lung adenocarcinoma treated with atezolizumab and later combined with brain radiation for brain metastasis. The subsequent abscopal effect first manifested as pseudoprogression of the primary lesion in the lung before remission was confirmed. This case suggests that immunotherapy increases the chance of an abscopal effect occurring after radiation therapy for brain metastases in patients with primary tumors with low immunogenicity.